A V-based 2 CT x MXene / In 2 O 3 Sensor material and preparation method thereof and its application in detecting Cl 2 Applications

Through the preparation of V2CTxMXene/In2O3 composite materials, the problems of poor detection sensitivity and high working temperature in the prior art are solved, and high sensitivity detection and room temperature monitoring of low concentration Cl2 are realized, reducing the detection cost.

CN118858386BActive Publication Date: 2024-12-17TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411347473.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-17
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

In the detection of Cl2, existing gas sensors have problems such as excessive working temperature, poor sensitivity, and difficulty in effectively detecting Cl2 at lower concentrations.

Method used

Using a sensor material based on V2CTxMXene/In2O3, V2AlC is mixed with an etchant and then ultrasonic, heated, washed, dried, and then reacted with dimethyl sulfoxide and sodium hydroxide solution to form a V2CTxMXene/In2O3 composite material, using it High specific surface area and rich functional group structure achieve high sensitivity detection of Cl2.

Benefits of technology

Highly sensitive detection of low-concentration Cl2 gas is achieved, which improves the response speed and selectivity of the sensor, can effectively monitor chlorine at room temperature, and reduces detection costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118858386B_ABST
    Figure CN118858386B_ABST
Patent Text Reader

Abstract

The present invention provides a V2CT-based x The sensor material of MXene / In2O3 and its preparation method and application in detecting Cl2 belong to the technical field of sensor devices. The present invention mixes V2AlC with an etchant and sequentially performs ultrasonication, heating, washing and drying to obtain a first material; mixes the first material with dimethyl sulfoxide and sequentially performs stirring, washing and drying to obtain a second material; mixes the second material with a sodium hydroxide solution and sequentially performs stirring, centrifugal precipitation, washing and drying to obtain V2CT x MXene; the V2CT x MXene composite nano-In2O3 to obtain V2CT x MXene / In2O3 sensor material, resulting V2CT x The MXene / In2O3 sensor material has a high specific surface area, broadens the reaction mechanism, improves the sensitivity of the sensor, and achieves highly sensitive detection of low-concentration Cl2 gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensor devices, and specifically relates to a sensor device based on V2CT. x MXene / In2O3 sensor materials, their preparation methods and their applications in detecting Cl2. Background Art

[0002] With the increasing attention paid to environmental protection and physical health in modern society, effective detection of toxic and harmful gases has become urgent. Using disinfectants for daily disinfection has become a must for every household, increasing the demand for industrial preparation of chlorine. Chlorine is a yellow-green toxic gas with a strong irritating odor. Long-term inhalation of chlorine may cause pneumonia, toxic pulmonary edema, damage to the bronchi, damage to the skin, etc. It is also soluble in water and can react with water in the human body to form corrosive acids. Gas sensors based on metal oxide semiconductors use chemical adsorption and desorption of gas molecules as a reaction mechanism. They have the characteristics of high sensitivity and rapid response. They are simple in structure and low in cost. They are one of the main types of gas sensors currently.

[0003] For chlorine gas sensing materials, common ones include In2O3, SnO2, ZnO and WO3. Among them, n-type semiconductor material In2O3 has important applications in toxic gas detection, solar cells and biosensors due to its wide band gap. MXene (two-dimensional metal carbide, nitride or carbonitride) is a new type of material recently discovered. It has attracted the attention and research of many researchers because of its unique two-dimensional layered structure, excellent metallic conductivity, rich surface functional groups and excellent surface controllable properties.

[0004] Compared with graphene, the advantage of MXene is that it has both covalent chemical bonds and ionic bonds and metallic bonds, which is more conducive to compounding with other materials. The diversity of chemical bonds provides more bonding advantages than graphene. Since 2011, people have discovered a variety of MXene, including Ti3C2, Ti2C, V2C, Ta4C3, Cr2TiC2, Nb2C and other types.

[0005] However, current gas sensors have problems in Cl2 detection, such as high operating temperature, poor sensitivity, and difficulty in effectively detecting lower concentrations of Cl2. Summary of the invention

[0006] In view of this, the present invention aims to provide a V2CT-based xThe sensor material of MXene / In2O3, its preparation method and application in detecting Cl2 have a high specific surface area, broaden the reaction mechanism, improve the sensitivity of the sensor, and achieve highly sensitive detection of low-concentration Cl2 gas.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides a V2CT-based x The preparation method of the MXene / In2O3 sensor material comprises the following steps:

[0009] S1. The V2AlC is mixed with an etchant and then subjected to ultrasound, heating, washing, and drying to obtain a first material;

[0010] S2. The first material is mixed with dimethyl sulfoxide and then stirred, washed and dried to obtain a second material;

[0011] S3. The second material is mixed with sodium hydroxide solution and then stirred, centrifuged, washed and dried to obtain V2CT x MXene;

[0012] S4. The V2CT x MXene composite nano-In2O3 to obtain V2CT x MXene / In2O3 sensor materials.

[0013] Preferably, the mass volume ratio of V2AlC to the etchant in S1 is 1-3 g: 10-50 mL;

[0014] The etchant is obtained by mixing sodium fluoride and 6 mol / L hydrochloric acid in a mass volume ratio of 1-3 g:10-50 mL.

[0015] Preferably, the ultrasonic time in S1 is 10-50 min.

[0016] Preferably, the heating temperature in S1 is 80-100°C, the heating time is 60-72 h, and the heating pressure is 6-12 MPa.

[0017] Preferably, the washing in S1 to S3 is performed independently by washing with deionized water; and the drying in S1 to S3 is performed independently by freeze drying.

[0018] Preferably, the mass volume ratio of the first material to dimethyl sulfoxide in S2 is 0.3-3 g: 10-100 mL.

[0019] Preferably, the stirring temperature in S2 is 15-30° C. and the stirring time is 20-24 h.

[0020] Preferably, the mass volume ratio of the second material to the sodium hydroxide solution in S3 is 0.3g:10-50mL.

[0021] Preferably, the stirring time in S3 is 1.5-3 h.

[0022] Preferably, the preparation method of nano-In2O3 in S3 is: In(NO3)3·4.5H2O, uric acid and diethylene glycol are mixed and subjected to hydrothermal reaction, cooling, washing and drying in sequence to obtain In2O3.

[0023] Preferably, V2CT in S4 x The method of MXene composite nano-In2O3 is any of the following methods:

[0024] Composite method 1:

[0025] In(NO3)3·4.5H2O and urea are weighed in a mass ratio of 1:3, and then dissolved in diethylene glycol and mixed for 2-4 hours, and then hydrothermally reacted at 200°C. After the hydrothermal reaction is completed, nano-In2O3 is obtained by cooling, washing and drying in sequence; the nano-In2O3 prepared by the present invention has a cubic structure such as Figure 5 As shown. This structure has a large specific surface area and a small particle size, which makes it easy to composite with MXene.

[0026] 50 mL of nano-In2O3 solution was mixed with 5 mg of polydiallyldimethylammonium chloride and then 50 mL of V2CTx MXene solution was added. V2CT was obtained by ultrasonication and drying. x MXene In2O3 sensor material; the nano-In2O3 solution is prepared by mixing nano-In2O3 with deionized water at a ratio of 1 mg:1 mL, and the V2CTx MXene solution is prepared by mixing V2CTx MXene with deionized water at a ratio of 1 mg:1 mL;

[0027] Composite method 2:

[0028] V2CT x MXene and deionized water were prepared into a solution at a ratio of 1 mg:1 mL, and then 50 mLV2CT x MXene was mixed with 5 mg of polydiallyldimethylammonium chloride and then freeze-dried to obtain V2CTx-P;

[0029] 1.222 g V2CTx-P, 1.222 g indium nitrate, 56 mL DEG and 3.2 mL H2O were mixed under nitrogen protection and ultrasonicated, and then 3.2 g urea was added and stirred for hydrothermal reaction. After cooling, it was washed with ethanol and deionized water in turn and freeze-dried to obtain V2CTx-P. x MXene / In2O3 sensor materials.

[0030] V2CT x MXene is considered as a potential gas sensor material due to its excellent conductivity, solution processability, and abundant surface functional groups. x Negatively charged, In2O3 material is negatively charged. The In2O3 material is modified by PDDA to make its surface positively charged. The two materials can be composited by electrostatic attraction. The characterization results show that In2O3 is evenly distributed on MXene (reference Figure 2 ), showing good selectivity and fast response and recovery to Cl2.

[0031] The present invention uses PDDA to modify the surface of MXene or In2O3 and then composites the two. In2O3 is a typical n-type semiconductor material with good gas-sensitive response characteristics, and the MXene surface after etching contains rich functional groups and a unique layered structure that provides a large specific surface area. From the BET and gas response test results, it can be seen that the composite material exhibits good characteristics in gas adsorption and response, thereby enhancing the gas-sensitive properties of the material.

[0032] In a second aspect, the present invention provides V2CT prepared by the above preparation method. x MXene / In2O3 sensor materials.

[0033] In a third aspect, the present invention provides the above-mentioned V2CT x Application of MXene / In2O3 sensor materials in detection of Cl2.

[0034] Preferably, the V2CT x The MXene / In2O3 sensor material detects Cl2 at concentrations above 100 ppb.

[0035] Contains at least the following beneficial technical effects:

[0036] 1. Preparation of V2CT by the present invention x The method of MXene / In2O3 semiconductor sensing materials is simple and low-cost;

[0037] 2. Since MXene materials have rich functional group structures and large specific surface areas, they can provide larger gas adsorption areas and more significant active sites, promoting the adsorption / desorption of Cl2 molecules and surface reactions;

[0038] 3. The present invention uses traditional In2O3 materials and composites them with the new two-dimensional material MXene to achieve monitoring and detection of chlorine at room temperature. Compared with In2O3, the composite material has a high specific surface area, broadens the reaction mechanism, improves the sensitivity of the sensor, and achieves high-sensitivity detection of low-concentration gases. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 V2CT x Schematic diagram of the preparation of MXene / In2O3 materials.

[0040] Figure 2 V2CT x Characterization results of MXene / In2O3 materials.

[0041] Figure 3 V2CT at room temperature x Sensitivity test chart of MXene / In2O3 material detecting Cl2.

[0042] Figure 4 This is the gas sensitive detection diagram for different concentrations of Cl2 at room temperature.

[0043] Figure 5 This is the microstructure diagram of nano-In2O3 prepared in Example 1. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0045] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0046] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.

[0047] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0048] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.

[0049] Example 1

[0050] This embodiment provides a V2CT x The preparation method of MXene / In2O3 material includes the following specific steps:

[0051] S1. Add 2 g of sodium fluoride to 25 mL of hydrochloric acid (6 mol / L) solution to obtain an etchant.

[0052] V2AlC (2 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 8 MPa and 90 °C for 72 h, then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0053] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0054] S3. Mix 0.3 g of the second material with 25 mL of sodium hydroxide solution (5 mol / L) and stir for 2 h, then centrifuge to obtain the precipitate, rinse with deionized water, and freeze-dry to obtain V2CT. x MXene;

[0055] S4. Preparation of In2O3 material: In(NO3)3·4.5H2O and urea were weighed in a mass ratio of 1:3, and then dissolved in diethylene glycol and mixed for 3 hours, and then subjected to hydrothermal reaction at 200°C. After the hydrothermal reaction was completed, nano-In2O3 was obtained by cooling, washing, and drying in sequence;

[0056] S5. The nano-In2O3 and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a nano-In2O3 solution, and the V2CTxMXene and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a V2CTx MXene solution;

[0057] Then, 10 wt% of polydiallyl dimethyl ammonium chloride was added to the nano-In2O3 solution for mixed modification, and then the nano-In2O3 solution and the V2CTx MXene solution were mixed according to the mass ratio of nano-In2O3 to V2CTx MXene of 1:2, and then subjected to ultrasound and drying to obtain V2CT x MXene In2O3 sensor material.

[0058] The resulting V2CT x The characterization results of MXene / In2O3 materials are as follows Figure 1 As shown;

[0059] The microstructure of the prepared nano-In2O3 is as follows Figure 5 shown.

[0060] Example 2

[0061] This embodiment provides a V2CT x The preparation method of MXene / In2O3 material includes the following specific steps:

[0062] S1. Add 1 g of sodium fluoride to 10 mL of hydrochloric acid (6 mol / L) solution to obtain an etchant.

[0063] V2AlC (1 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 6 MPa and 90 °C for 72 h, then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0064] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0065] S3. Mix 0.3 g of the second material with 10 mL of sodium hydroxide solution (5 mol / L) and stir for 2 h, then centrifuge to obtain the precipitate, rinse with deionized water, and freeze-dry to obtain V2CT. x MXene;

[0066] S4. Preparation of In2O3 material: In(NO3)3·4.5H2O and urea were weighed in a mass ratio of 1:3, and then dissolved in diethylene glycol and mixed for 2h, and then subjected to hydrothermal reaction at 200°C. After the hydrothermal reaction was completed, nano-In2O3 was obtained by cooling, washing and drying in sequence;

[0067] S5. The nano-In2O3 and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a nano-In2O3 solution, and the V2CTxMXene and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a V2CTx MXene solution;

[0068] Then, 10 wt% of polydiallyl dimethyl ammonium chloride was added to the nano-In2O3 solution for mixed modification, and then the nano-In2O3 solution and the V2CTx MXene solution were mixed according to the mass ratio of nano-In2O3 to V2CTx MXene of 1:2, and then subjected to ultrasound and drying to obtain V2CT x MXene In2O3 sensor material.

[0069] Example 3

[0070] This embodiment provides a V2CT x The preparation method of MXene / In2O3 material includes the following specific steps:

[0071] S1. Add 3 g of sodium fluoride to 50 mL of hydrochloric acid (6 mol / L) solution to obtain an etchant.

[0072] V2AlC (3 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 12 MPa and 90 °C for 72 h, then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0073] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0074] S3. Mix 0.3 g of the second material with 50 mL of sodium hydroxide solution (5 mol / L) and stir for 2 h, then centrifuge to obtain the precipitate, rinse with deionized water, and freeze-dry to obtain V2CT. x MXene;

[0075] S4. Preparation of In2O3 material: In(NO3)3·4.5H2O and urea were weighed in a mass ratio of 1:3, and then dissolved in diethylene glycol and mixed for 4 hours, and then subjected to a hydrothermal reaction at 200°C. After the hydrothermal reaction was completed, nano-In2O3 was obtained by cooling, washing, and drying;

[0076] S5. The nano-In2O3 and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a nano-In2O3 solution, and the V2CTxMXene and deionized water are mixed at a ratio of 1 mg: 1 mL to prepare a V2CTx MXene solution;

[0077] Then, 10 wt% of polydiallyl dimethyl ammonium chloride was added to the nano-In2O3 solution for mixed modification, and then the nano-In2O3 solution and the V2CTx MXene solution were mixed according to the mass ratio of nano-In2O3 to V2CTx MXene of 1:2, and then subjected to ultrasound and drying to obtain V2CT x MXene In2O3 sensor material.

[0078] Example 4

[0079] This embodiment provides a V2CT x The preparation method of MXene / In2O3 material includes the following specific steps:

[0080] S1. Add 3 g of sodium fluoride to 50 mL of hydrochloric acid (6 mol / L) solution to obtain an etchant.

[0081] V2AlC (3 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 8 MPa and 90 °C for 72 h, then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0082] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0083] S3. Mix 0.3 g of the second material with 50 mL of sodium hydroxide solution (5 mol / L) and stir for 2 h, then centrifuge to obtain the precipitate, rinse with deionized water, and freeze-dry to obtain V2CT. x MXene;

[0084] S4. V2CT x MXene and deionized water were prepared into a solution at a ratio of 1 mg:1 mL and then placed in V2CT x 10 wt% of polydiallyldimethylammonium chloride was added to the MXene solution, mixed and modified, and then freeze-dried to obtain V2CTx-P;

[0085] V2CTx-P, indium nitrate, DEG and H2O were weighed and mixed, and then ultrasonicated under nitrogen protection, and then urea was added and stirred for hydrothermal reaction. After cooling, it was washed with ethanol and deionized water in turn, and freeze-dried to obtain V2CT x MXene / In2O3 sensor materials;

[0086] The mass volume ratio of the V2CTx-P, indium nitrate, DEG, H2O, and urea is 1.2g:1.2g:56mL:3.2mL:3.2g.

[0087] Test Example 1

[0088] The V2CT obtained in Example 1-3 x MXene / In2O3 material is prepared into gas sensor.

[0089] The preparation method is:

[0090] Add 0.2 mL of dispersant (deionized water) into the mortar;

[0091] Add V2CT in small amounts and multiple times x MXene / In2O3 material, a total of 0.5 g was added;

[0092] Grind until it becomes a thin paste;

[0093] A sensitive film with an area of ​​0.75*0.75 cm and a thickness of 5-10 μm is formed on the Pt electrode coating and aged at room temperature for 7-14 days to assemble into a sensor.

[0094] Test Example 2

[0095] The V2CT for Cl2 detection was tested using an optoelectronic integrated test platform. x The MXene / In2O3 semiconductor sensor is used for Cl2 gas sensing test, including the following steps:

[0096] Step (1): V2CT in Example 1 x The semiconductor sensor made of MXene / In2O3 was connected to the gas-sensitive test system, with an operating voltage of 5V and an operating temperature set to room temperature;

[0097] Step (ii): At room temperature, Cl2 is introduced into the gas chamber at 50-100 s; the resistance of the V2CTx MXene / In2O3 semiconductor sensor used for Cl2 detection changes after the introduction of chlorine gas, and its response curve is observed;

[0098] Step (III): After a period of response, open the air chamber; re-introduce air and observe the resistance value starting to recover until it returns to the initial state. Perform 5 to 6 cycles of testing;

[0099] The test results are as follows Figure 3 As shown, the experiment shows that using V2CT x As a gas-sensitive material, MXene / In2O3 shows high sensitivity to Cl2 and responds quickly.

[0100] Test Example 3

[0101] In this test example, the V2CT obtained for Cl2 detection x The MXene / In2O3 semiconductor sensor was subjected to a Cl2 gas-sensing test, and the test method was referred to Experimental Example 2. The working temperature was selected as room temperature, and gas-sensing detection was performed on Cl2 at different concentrations of 200 ppb-1000 ppb.

[0102] like Figure 4 As shown in the figure, the experimental results show that the In2O3 semiconductor sensor used for Cl2 detection exhibits high sensitivity in the detection of low-concentration Cl2 below 1ppm (100ppb-1ppm), which is beneficial for the quantitative analysis and calibration of low-concentration Cl2 gas.

[0103] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method based on V2CT x The method for preparing a MXene / In2O3 sensor material is characterized in that: The following steps are involved: S1. The V2AlC is mixed with an etchant and then subjected to ultrasound, heating, washing, and drying to obtain a first material; S2. The first material is mixed with dimethyl sulfoxide and then stirred, washed and dried to obtain a second material; S3. The second material is mixed with sodium hydroxide solution and then stirred, centrifuged, washed and dried to obtain V2CT x MXene; S4. The V2CT x MXene composite nano-In2O3 to obtain V2CT x MXene / In2O3 sensor materials; The S4 V2 CT x The method of MXene composite nano-In2O3 is any of the following methods: Composite method 1: In(NO3)3·4.5H2O and urea were weighed in a mass ratio of 1:3, and then dissolved in diethylene glycol and mixed for 2-4 hours, and then hydrothermally reacted at 200°C. After the hydrothermal reaction was completed, nano-In2O3 was obtained by cooling, washing and drying in sequence; The nano-In2O3 and deionized water were mixed into a nano-In2O3 solution at a ratio of 1 mg:1 mL. x MXene and deionized water were mixed into V2CT at a ratio of 1 mg:1 mL. x MXene solution; Then, 10 wt% of polydiallyl dimethyl ammonium chloride was added to the nano-In2O3 solution and mixed and modified according to the nano-In2O3: V2CT x MXene mass ratio 1:2 nano-In2O3 solution and V2CT x MXene solution mixing, ultrasonication and drying to obtain V2CT x MXene In2O3 sensor material; Composite method 2: V2CT x MXene and deionized water were prepared into a solution at a ratio of 1 mg:1 mL and then placed in V2CT x 10 wt% of polydiallyldimethylammonium chloride was added to the MXene solution, mixed and modified, and then freeze-dried to obtain V2CTx-P; V2CTx-P, indium nitrate, DEG and H2O were weighed and mixed, and then ultrasonicated under nitrogen protection, and then urea was added and stirred for hydrothermal reaction. After cooling, it was washed with ethanol and deionized water in turn, and freeze-dried to obtain V2CT x MXene / In2O3 sensor materials; The mass volume ratio of V2CTx-P, indium nitrate, DEG, H2O, and urea is 1.2g:1.2g:56mL:3.2mL:3.2g; The V2CT x MXene / In2O3 sensor material is used in the detection of Cl2, the V2CT x The MXene / In2O3 sensor material detects Cl2 at concentrations above 100 ppb.

2. The preparation method according to claim 1, characterized in that: The mass volume ratio of V2AlC to the etchant in S1 is 1~3 g:10~50 mL; The etchant is obtained by mixing sodium fluoride and 6 mol / L hydrochloric acid in a mass volume ratio of 1-3 g:10-50 mL.

3. The preparation method according to claim 1, characterized in that: In the S1, the heating temperature is 80-100°C, the heating time is 60-72 h, and the heating pressure is 6-12 MPa.

4. The preparation method according to claim 1, characterized in that: The mass volume ratio of the first material to dimethyl sulfoxide in S2 is 0.3-3 g: 10-100 mL.

5. The preparation method according to claim 1, characterized in that: The stirring temperature in S2 is 15-30°C and the stirring time is 20-24 h.

6. The preparation method according to claim 1, characterized in that: The mass volume ratio of the second material to the sodium hydroxide solution in S3 is 0.3g:10-50mL.

7. The preparation method according to claim 1, characterized in that: The preparation method of nano-In2O3 in S4 is: In(NO3)3·4.5H2O, uric acid and diethylene glycol are mixed and subjected to hydrothermal reaction in sequence, followed by cooling, washing and drying to obtain In2O3.

8. V2CT prepared by the preparation method according to any one of claims 1 to 7 x MXene / In2O3 sensor materials.

9. The V2CT according to claim 8 x Application of MXene In2O3 sensor materials in detection of Cl2.